The Effect Game Based Learning Model Using Educaplay on Elementary School Students’ IPAS Learning Outcomes - efpritiara; Kiki Aryaningrum; Aldora Pratama (Journal of Education and Teaching Learning, 2026)
This study aims to determine whether there is an effect of the IPAS learning model on learning outcomes in the subject of Indonesian cultural heritage using a game-based learning model supported by Educaplay media for fourth-grade students at SD Negeri 55 Prabumulih. This study employed a quasi-experimental design with a nonequivalent control group design. The study population consisted of all 41 fourth-grade students at SD Negeri 55 Prabumulih. The sample comprised Class IV A as the control group (21 students) and Class IV B as the experimental group (20 students). Data collection was conducted using tests. Data analysis techniques included normality tests, homogeneity tests, hypothesis testing, and N-Gain tests. The results showed a calculated t-value of 5.139, which was greater than the critical t-value of 2.023, with a significance level of 0.00 (less than 0.05). The calculated N-Gain score for the experimental class was 0.70, which falls into the high category, and the N-Gain percentage was 70.94%, which is considered sufficiently effective for use in learning activities. Therefore, it is concluded that there is an effect of the game-based learning model assisted by Educaplay media on improving IPAS learning outcomes regarding Indonesian cultural heritage material among fourth-grade students at SD Negeri 55 Prabumulih.